PENGARUH PERIODONTITIS TERHADAP KESEHATAN BAYI YANG DILAHIRKAN : INFLUENCE OF PERIODONTITIS ON THE HEALTH OF BABIES BORN - Irma Ervina; Ellissa Wijaya (Dentika: Dental Journal, 2010)
Periodontal disease is characterised by low-grade infection of the gums and tooth support structures by Gram-negative, predominantly anaerobic bacteria. Periodontitis may cause preterm birth by causing low-grade bacteraemia, which lodges in the decidua, chorion and amnion or by releasing endotoxin into the maternal circulation, which triggers intrauterine inflammation and preterm birth. Approximately 25% of PLBW cases occur without any of the known risk factors, which have prompted continuation of the search for other possible causal factors. Collectively, the studies summarized in this paper suggest a model wherein chronic periodontal infection, serving as a reservoir for bacterial products (such as LPS) or various inflammatory mediators (or both), may play an important role in the development of PLBW. On that basis, the authors felt the need for further review on the effect of periodontitis on the health of babies born, and is expected to provide insight into the influence of periodontitis on the health of babies born so the dentist can be more critical and increasing role in preventing and improving maternal health pregnancy and abortion standarizations. As conclusion, the poor health of periodontium during pregnancy is one of the risks of preterm and low birth weight